1988
DOI: 10.1055/s-2007-1018165
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Ruber Mucosae with Esophageal Involvement

Abstract: The clinical course of a 50-year-old woman with oral lichen ruber planus (Irp) and prolonged dysphagia is described. The swallowing problems of this patient were related to an inflammatory lesion of the middle third of the esophagus, leading to stenosis. Distal to this area, the esophagus was covered with mucosa of the cardia type, as seen in endobrachyesophagus. Apart from reflux disease, the Irp may have accounted for the stenosis of the mid-esophagus. The mucosal lesions disappeared after administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Retinoid therapy was successful in only 1 of the 4 cases reported [13], and moreover, it was hardly tolerated by the patients [20, 22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinoid therapy was successful in only 1 of the 4 cases reported [13], and moreover, it was hardly tolerated by the patients [20, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…Oesophageal involvement in lichen planus is very rare, only 17 cases [7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22]and a series of 6 patients in 15 years from the Mayo Clinic [23]have been reported in the literature so far. This complication is probably underestimated, since a small study in 1990 on 19 patients with OLP demonstrated that a quarter of those had oesophageal involvement [24](table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Different systemic therapies are described. Systemic corticosteroids are supposed to be most effective as well as retinoids, cyclosporine, azathioprine, tacrolimus, rituximab and griseofulvin or intralesional corticosteroids [71,72,76,77,78,79,80,81,82,83,84,85,86]. …”
Section: Discussionmentioning
confidence: 99%
“…Dilation is commonly used despite concerns about worsening esophageal stenosis or oral lesions due to Koebner phenomenon. Other regimens described include adrenocorticotropic hormone injections, oral corticosteroids, etretinate, and topical corticosteroids 1,11–23 . Topical tacrolimus, a potent inactivator of T‐lymphocytes used initially in patients with transplants, was successful for oral lichen planus in six patients 24–26 Table 3.…”
Section: Treatmentmentioning
confidence: 99%